Pricing Chinese rain: A multisite mulit-period equilibrium pricing model for rainfall derivatives - Wolfgang Karl Härdle; Maria Osipenko (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
Many industries are exposed to weather risk which they can transfer on financial markets via weather derivatives. Equilibrium models based on partial market clearing became a useful tool for pricing such kind of financial instruments. In a multi-period equilibrium pricing model agents rebalance their portfolio of weather bonds and a risk free asset in each period such that they maximize the expected utility of their incomes constituted by possibly weather dependent profits and payoffs of portfolio positions. We extend the model to a multisite version and apply it to pricing rainfall derivatives for Chinese provinces. By simulating realistic market conditions with two agent types, farmers with profits highly exposed to weather risk and a financial investor diversifying her financial portfolio, we obtain equilibrium prices for weather derivatives on cumulative monthly rainfall. Dynamic portfolio optimization under market clearing and utility indifference of these representative agents determines equilibrium quantity and price for rainfall derivatives.
Keywords: C22; C51; G13; 330; rainfall derivatives; equilibrium pricing; space-time Markov model; Wetter; Finanzderivat; Region; Optionspreistheorie; Portfolio-Management; China